Effects of short-duration spaceflight on the execution of critical mission tasks - Clément, Gilles; Moudy, Sarah; Macaulay, Timothy R.; Wood, Scott J. (Frontiers in Physiology, 2025)
BackgroundThe objective of this study was to investigate how short-duration spaceflight affects private astronauts’ performance of mission-critical functional tasks that challenge balance and locomotor control systems shortly after they return to Earth.MethodsTen astronauts were assessed while they performed three functional tests (sit-to-stand, tandem walk, and walk-and-turn) before spaceflight and a few hours after returning from missions lasting from 4 to 21 days. Their performance was compared to that of 36 astronauts who returned from long-duration missions lasting from 6 to 12 months.ResultsShortly after return from a short-duration spaceflight, astronauts had difficulty standing, walking, and turning around obstacles, and they experienced terrestrial readaptation motion sickness. However, the performance of these functional tasks was less impacted after short-duration missions than after long-duration missions. After long-duration spaceflight, astronauts took longer to stabilize when standing, made fewer correct steps in balance tests (especially with eyes closed), needed more time for walking tasks, and turned more slowly than after short-duration flight. Motion sickness ratings were more variable and often higher in the long-duration group.ConclusionSimilar to long-duration spaceflight, short-duration missions can also result in significant postflight vestibular and sensorimotor impairments, potentially affecting the ability of some crewmembers to perform critical mission tasks.